Irony's architecture: Reflections on a photographic research project - Sayers, Janet; Bathurst, Ralph; Symonds, Henry (Massey University. Department of Management and International Business, 2007)
This paper presents a research approach based on irony, rather than certainty. Using Richard Rorty's conception of irony, we contend that much traditional research in management presents a final language which is implicit in both the construction of a research method and its final presentation as findings. This paper suggests we should take irony more seriously, and deliberately construct research to allow and encourage re-description by our research's final arbiters - its readers, and even its subjects. Further, we advocate that by inviting irony into our work, we encourage greater identification between ourselves, our audience of readers, and the subjects of our work. We illustrate our argument by reflecting on a recent photographic research project which was a collaborative effort between management researchers and an artist. We show how the simple architecture of this project was built from doubt and how irony is communicated through the pictures. We then show how photography can be a useful technique that encourages readers to engage in re-description of petit récits (small stories), told through images. We discuss our reflections by focusing on the implications of our research for management education.
Keywords: Photographs; Art research methods; Fields of Research::350000 Commerce, Management, Tourism and Services